2009
DOI: 10.1017/s0317167100008106
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cognitive Impairment and Dementia Using the Animal Fluency Test: The DECIDE Study

Abstract: Dementia rates increase with age; 1 an analysis of 22 studies reported a doubling of dementia prevalence rates every 5.1 years until the age of 95. 2 The yearly incidence of dementia in Canada, among individuals aged 65 years and older, is estimated at 19.1/1000 for men and 21.8/1000 for women. 3 The prevalence of dementia is expected to increase over the next decades, as a result of the aging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The present study extended the abovementioned results of non-linear relationship to a simple yet widely used neuropsychological test for the detection of dementia: SF (more specifically, animal fluency) test. SF performance has been linked to medial temporal lobe (MTL) and anterior temporal cortex (Pelletier et al, 2017), and there is a large body of evidence supporting a diagnostic role of SF test in dementia (Sebaldt et al, 2009;Sutin et al, 2019), including AD (Henry et al, 2004). However, few studies have identified a significant relationship between cholesterol level and SF performance.…”
Section: Discussionmentioning
confidence: 99%
“…The present study extended the abovementioned results of non-linear relationship to a simple yet widely used neuropsychological test for the detection of dementia: SF (more specifically, animal fluency) test. SF performance has been linked to medial temporal lobe (MTL) and anterior temporal cortex (Pelletier et al, 2017), and there is a large body of evidence supporting a diagnostic role of SF test in dementia (Sebaldt et al, 2009;Sutin et al, 2019), including AD (Henry et al, 2004). However, few studies have identified a significant relationship between cholesterol level and SF performance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who recalled less than 15 animals were deemed not appropriate for this study. The animal fluency test has a sensitivity of 88% and specificity of 96% in detecting cognitive impairment (10). Sampling for variation in gender, age, race, and the admitting hospital unit (i.e., cardiac, medicine, and surgery) was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] The study participants' cognitive function was assessed using the Mini-Mental State Examination (MMSE), Alzheimer's Disease Assessment Scale (ADAS) items 1-3 (measure of episodic memory delayed recall), A Quick Test of Cognitive Speed (AQT; measure of cognitive processing speed), and the 1-minute Animal Fluency test. [17][18][19][20] At each study visit, a thorough medical history was taken and the patients underwent extensive testing in both motor symptoms and cognition. The baseline data of the study participants in the present study have previously been described in Hall et al, 5 2012, where they were part of a larger cohort.…”
mentioning
confidence: 99%